2012
DOI: 10.5180/jsgoe.28.581
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Ectopic Pregnancy in Ipsilateral Fallopian tube after Laparoscopic Corneal Resection for an Interstitial Pregnancy: Case report and Literature Review

Abstract: An interstitial pregnancy accounts for only 1-2.5% of tubal pregnancies; however, the incidence of interstitial pregnancies is increasing as a result of artificial reproductive technology and the spread of sexually transmitted diseases such as Chlamydia tracomatis. Because of the difficulty of early diagnosis, the mortality rate of interstitial pregnancies is higher than that of other sites. We report a rare case of repeat ectopic pregnancy in the ipsilateral fallopian tube after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A case of cornual pregnancy was reported previously in which the fallopian tube was preserved by performing cornual wedge resection; however, this patient experienced a recurrent ectopic pregnancy in the ampullar region of the ipsilateral uterine tube. [ 8 ] In cornual pregnancy, a previous study recommends tubal resection and sufficient coagulation of the cornual region. However, it has been reported that coagulation after tubal resection weakens the muscle layer and causes placenta accreta.…”
Section: Discussionmentioning
confidence: 99%
“…A case of cornual pregnancy was reported previously in which the fallopian tube was preserved by performing cornual wedge resection; however, this patient experienced a recurrent ectopic pregnancy in the ampullar region of the ipsilateral uterine tube. [ 8 ] In cornual pregnancy, a previous study recommends tubal resection and sufficient coagulation of the cornual region. However, it has been reported that coagulation after tubal resection weakens the muscle layer and causes placenta accreta.…”
Section: Discussionmentioning
confidence: 99%